2023
DOI: 10.1039/d3ma00159h
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in nano-based antidiabetic therapeutics: a path to effective diabetes management

Abstract: Diabetes mellitus is characterized by altered blood sugar homeostasis. A chronic metabolic disorder affecting millions of people worldwide. Diabetic mortality rates are escalating in developed countries by the clock. Till...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 165 publications
(249 reference statements)
0
5
0
1
Order By: Relevance
“…A detailed description of functionalized peptide-based nanoparticles as cancer nanotherapeutics is summarized by Sharma and co-workers. 68 One such promising peptide nanodrug was formulated by the Zhang group using a dual-targeting RGD-conjugated KLAK peptide probe, and self-assembled into spherical, small size (30−40 nm) to form f-SAPNs through a pH-sensitive synthesis approach as a schematic illustration depicted in Figure 3. 69 This nanoprobe was observed to possess enhanced receptor-specific targetability, improved internalization capabilities, and up to a 3.76% degree of apoptosis, and in vivo therapeutic studies revealed that these SAPNs decrease the tumor size 2-fold compared with its parent molecular structure.…”
Section: Lipophilic Naturementioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of functionalized peptide-based nanoparticles as cancer nanotherapeutics is summarized by Sharma and co-workers. 68 One such promising peptide nanodrug was formulated by the Zhang group using a dual-targeting RGD-conjugated KLAK peptide probe, and self-assembled into spherical, small size (30−40 nm) to form f-SAPNs through a pH-sensitive synthesis approach as a schematic illustration depicted in Figure 3. 69 This nanoprobe was observed to possess enhanced receptor-specific targetability, improved internalization capabilities, and up to a 3.76% degree of apoptosis, and in vivo therapeutic studies revealed that these SAPNs decrease the tumor size 2-fold compared with its parent molecular structure.…”
Section: Lipophilic Naturementioning
confidence: 99%
“…It is considered as a diagnostic technique used for personalized therapeutic interventions by employing targeted molecular vectors as a delivery system for payloads via incorporation of diagnostic and therapeutic functionalities. 157 The example of diagnostic phase of theranostics is 68 Ga-DOTATOC�a promising radioactive diagnostic drug that targets to SSTR2-receptor overexpressed on neuroendocrine tumors and the tumor will light-up on a PET technique. Once the cancer is diagnosed, the Ga-68 replaced by radionuclides of prolong half-life such as Lu-177 (Lutathera), In-111, I-131 (Azedra), or Y-90 to target, damaging cell's DNA and killing the tumor cells expressing SSTR2-receptors�it is the therapeutic phase of theranostics.…”
Section: Theranosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, los medicamentos utilizados para tratar a pacientes con Diabetes mellitus tipo 2 tienen algunos efectos adversos 4 . Nuevos medicamentos a base en nanotecnología se utilizan como terapias emergentes para un control efectivo de la Diabetes mellitus tipo 2 7 . Estudios han demostrado que ciertas plantas presentan efectos hipoglucémicos: algas 8 , hojas de Dodecadenia grandiflora (Lauraceae) 9 , flavonoides presentes en Artemisia dracunculus 10 , frutos Pongamia pinnata 11 , melon (Momordica charantia) [12][13][14] .…”
Section: Introductionunclassified